2017
DOI: 10.25115/ejrep.v7i19.1351
|View full text |Cite
|
Sign up to set email alerts
|

Predicting First Year University Students’ Academic Success

Abstract: Introduction: Premature withdrawal from university due to academic failure can present

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
2
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 16 publications
6
33
2
9
Order By: Relevance
“…Previous studies involving post-secondary students have demonstrated that some of the key determinants include gender (Baker, 2004;Clifton, 1997;Keller, Crouse, & Trusheim, 1993;Mau & Lynn, 2001), socio-economic status (Hansen & Mastekaasa, 2006;Ross, Cleland, & MacLeod, 2006), employment status (Applegate & Daly, 2006;Hunt, Lincoln, & Walker, 2004), high school grades (DeBerard, Spielmans, & Julka, 2004;Duff, 2004;Hall, Smith, & Chia, 2008;Mattson, 2007;Olani, 2009;Zwick & Sklar, 2005), high school environment (Pike & Saupe, 2002;Wolniak & Engberg, 2010), personality traits (Musgrave-Marquart, Bromley, & Dalley, 1997;Nguyen, Allen, & Fraccastoro, 2005;Ridgell & Lounsbury, 2004;Tross, Harper, Osher, & Kneidinger, 2000), health status (Mattison, 2006;Trockel, Barnes, & Egget, 2000), satisfaction with academic life (Chambel & Curral, 2005;Graunke & Woosley, 2005), amount of time devoted to study (Jackson, Weiss, Lundquist, & Hooper, 2003;Nonis & Hudson, 2006), styles of learning (Diseth, 2002;Wilding & Andrews, 2006), achievement motivation (Morris, Brooke, & May, 2003;Roebken, 2007;Steinberg, 2006), and social support (Clifton, Perry, Roberts, & Peter, 2008;Cutrona, Cole, Colangelo, Assouline, & Russell, 1994;Orpen, 1996;Spitzer, 2000;Walker & Satterwhite, 2002 …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies involving post-secondary students have demonstrated that some of the key determinants include gender (Baker, 2004;Clifton, 1997;Keller, Crouse, & Trusheim, 1993;Mau & Lynn, 2001), socio-economic status (Hansen & Mastekaasa, 2006;Ross, Cleland, & MacLeod, 2006), employment status (Applegate & Daly, 2006;Hunt, Lincoln, & Walker, 2004), high school grades (DeBerard, Spielmans, & Julka, 2004;Duff, 2004;Hall, Smith, & Chia, 2008;Mattson, 2007;Olani, 2009;Zwick & Sklar, 2005), high school environment (Pike & Saupe, 2002;Wolniak & Engberg, 2010), personality traits (Musgrave-Marquart, Bromley, & Dalley, 1997;Nguyen, Allen, & Fraccastoro, 2005;Ridgell & Lounsbury, 2004;Tross, Harper, Osher, & Kneidinger, 2000), health status (Mattison, 2006;Trockel, Barnes, & Egget, 2000), satisfaction with academic life (Chambel & Curral, 2005;Graunke & Woosley, 2005), amount of time devoted to study (Jackson, Weiss, Lundquist, & Hooper, 2003;Nonis & Hudson, 2006), styles of learning (Diseth, 2002;Wilding & Andrews, 2006), achievement motivation (Morris, Brooke, & May, 2003;Roebken, 2007;Steinberg, 2006), and social support (Clifton, Perry, Roberts, & Peter, 2008;Cutrona, Cole, Colangelo, Assouline, & Russell, 1994;Orpen, 1996;Spitzer, 2000;Walker & Satterwhite, 2002 …”
Section: Introductionmentioning
confidence: 99%
“…Lo cual se considera muy importante, ya que como indican otros estudios (Le et al, 2005;Olani, 2009), las variables motivacionales son un factor complementario a los parámetros tradicionales que puede contribuir a la mejora del desempeño posterior de los alumnos. De manera específica, tal como plantean Kaplan, Lichtinger y Gorodetsky (2009), se debe poner una especial atención a las orientaciones motivacionales que los alumnos adoptan en cada contexto educativo, así como a las diferentes estrategias que los alumnos consideran relevantes para involucrarse académicamente cuando adoptan diferentes orientaciones motivacionales.…”
Section: Discussionunclassified
“…Sin embargo, varios investigadores (Le, Casillas, Robbins y Langley, 2005;Olani, 2009) argumentan que dichas evaluaciones, aunque necesarias, por sí solas no predicen el desempeño académico posterior de los alumnos. Lo mismo sucede con otros predictores tradicionales como el promedio académico previo.…”
Section: Conocimientos Previosunclassified
“…These motivational factors influence the development of adequate statistical thinking during the teaching and learning process, the structural application of the knowledge obtained in real life situations, and a future interest in statistics (Gal & Ginsburg, 1994). This is because self-and task value beliefs play a central role in student"s effort, persistence, and perseverance to study; and an individual who expects to do well in an activity and has high value for that task would be expected to choose that task over others and to display high effort and persistence for that task (Eccles & Wigfield, 1995;Lent, Brown & Hackett, 2000;Olani, 2009). …”
Section: Conceptual Frameworkmentioning
confidence: 99%